2020
DOI: 10.1177/1941738119887396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Physical Therapy Protocols Between Open Latarjet Coracoid Transfer and Arthroscopic Bankart Repair

Abstract: Context: Recent studies examining return to sport after traumatic shoulder instability suggest faster return-to-sport time lines after bony stabilization when compared with soft tissue stabilization. The purpose of the current study was to define variability across online Latarjet rehabilitation protocols and to compare Latarjet with Bankart repair rehabilitation time lines. Evidence Acquisition: Online searches were utilized to identify publicly available rehabilitation protocols from Accreditation Council fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Rehabilitation after open Latarjet surgery currently remains a matter of surgeon preference rather than driven by a scientific rationale. Rehabilitation is therefore subject to high variability between centers [ 47 ]. Only a single study reported short-term outcomes of immediate self-rehabilitation after open Latarjet surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rehabilitation after open Latarjet surgery currently remains a matter of surgeon preference rather than driven by a scientific rationale. Rehabilitation is therefore subject to high variability between centers [ 47 ]. Only a single study reported short-term outcomes of immediate self-rehabilitation after open Latarjet surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A fast return to activity and sport seems most suitable. At the same time, the goal of a postoperative sling is to balance the risk inherent to excessive traction onto the coracoid process and stiffness secondary to immobilization, preventing timely return to play in athletes [ 47 , 50 ]. To our knowledge, all current rehabilitation protocols rely on a sling immobilization [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rehabilitation after open Latarjet surgery currently remains a matter of surgeon preference rather than driven by a scienti c rationale. Rehabilitation is therefore subject to high variability between centers (42). Only a single study reported short-term outcomes of immediate self-rehabilitation after open surgery (23).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the goal of a postoperative sling is to balance the risk inherent to excessive traction onto the coracoid process and stiffness secondary to immobilization, preventing timely return to play in athletes (42,45). To our knowledge, all current rehabilitation protocols rely on a sling immobilization (42). A recent systematic review evaluated an 83.6% rate of return to sport at a mean time of 5 months (44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation